2021
DOI: 10.3389/fnut.2021.647748
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Pressure Homogenization on Pectin Structure and Cloud Stability of Not-From-Concentrate Orange Juice

Abstract: Not-from-concentrate (NFC) juice is popular with consumers due to its similarity to fresh fruit juice in taste, flavor, and beneficial nutrients. As a commonly used technology in fruit juice production, high-pressure homogenization (HPH) can enhance the commercial value of juice by improving the color, flavor, taste, and nutrient contents. In this study, the effects of HPH on the pectin structural properties and stability of NFC orange juice were investigated. The correlations between HPH-induced changes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Augusto et al (2012) reported it and described that the effect of homogenization pressure on the disruption of suspended particles seems to follow an asymptotic behavior. The same conclusion was drawn, and it was pointed out that the changes in particle size caused by increased pressure at high pressure were smaller than that caused by increased pressure at low pressure (Yu et al, 2021). In fact, this can even be observed in the D [3,2] and [4,3] values in Table 2.…”
Section: Particle Size Analysissupporting
confidence: 63%
See 1 more Smart Citation
“…Augusto et al (2012) reported it and described that the effect of homogenization pressure on the disruption of suspended particles seems to follow an asymptotic behavior. The same conclusion was drawn, and it was pointed out that the changes in particle size caused by increased pressure at high pressure were smaller than that caused by increased pressure at low pressure (Yu et al, 2021). In fact, this can even be observed in the D [3,2] and [4,3] values in Table 2.…”
Section: Particle Size Analysissupporting
confidence: 63%
“…( 2019 ) and carrot beverage by Yu et al. ( 2021 ). However, with the increase of temperature, the suspension stability showed a trend of first increase, then decrease and then increase, which was related to the change of particle aggregation and fragmentation, and corresponded to the results of particle size.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, larger aggregates are formed, leading to faster sedimentation (Silva et al, 2010). Storage did not significantly change SI of IF (−5 • C/73 MPa) (p < 0.05), indicating that the juice became more stable (Yu et al, 2021) exposed to higher pressure became more difficult to precipitate. High pressure during IF might cause a reduction in particle size, creating more uniform particles (Anema et al, 2005).…”
Section: Pulp Sedimentation and Sedimentation Indexmentioning
confidence: 94%
“…Relevant studies have shown [ 123 , 124 ] that high-pressure homogenization has no significant effect on the pH value, soluble solids, and organic acid content of juice. However, it will lead to a reduction in titratable acid content and a change in the color of the juice.…”
Section: Aronia Melanocarpa Juice Processing Technologymentioning
confidence: 99%